Patients in long-term maintenance therapy for drug use in Italy: analysis of some parameters of social integration and serological status for infectious diseases in a cohort of 1091 patients - Montanari Linda; GICS; Pattaro Cristian; Lugoboni Fabio; Quaglio Gianluca; Lechi Alessandro; Mezzelani Paolo; Des Jarlais Don C (BMC, 2006)
Abstract Background Heroin addiction often severely disrupts normal social functioning. The aims of this multi-centre study of heroin users in long-term replacement treatment were: i) to provide information on aspects of social condition such as employment, educational background, living status, partner status and any history of drug addiction for partners, comparing these data with that of the general population; ii) to assess the prevalence of hepatitis, syphilis and HIV, because serological status could be a reflection of the social conditions of patients undergoing replacement treatment for drug addiction; iii) to analyse possible relationships between social conditions and serological status. Methods A cross-sectional study was carried out in sixteen National Health Service Drug Addiction Units in northern Italy. The data were collected from February 1, 2002 to August 31, 2002. Recruitment eligibility was: maintenance treatment with methadone or buprenorphine, treatment for the previous six months, and at least 18 years of age. In the centres involved in the study no specific criteria or regulations were established concerning the duration of replacement therapy. Participants underwent a face-to-face interview. Results The conditions of 1091 drug treatment patients were evaluated. The mean duration of drug use was 14.5 years. Duration was shorter in females, in subjects with a higher educational background, and in stable relationships. Most (68%) had completed middle school (11-14 years of age). Seventy-nine percent were employed and 16% were unemployed. Fifty percent lived with their parents, 34% with a partner and 14% alone. Males lived more frequently with their parents (55%), and females more frequently with a partner (60%). Sixty-seven percent of male patients with a stable relationship had a partner who had never used heroin. HCV prevalence was 72%, HBV antibodies were detected in 42% of patients, while 30% had been vaccinated; 12.5% of subjects were HIV positive and 1.5% were positive for TPHA. Conclusion A significant percentage of heroin users in treatment for opiate addiction in the cohort study have characteristics which indicate reasonable integration within broader society. We posit that the combination of effective treatment and a setting of economic prosperity may enhance the social integration of patients with a history of heroin use.